A clinico-etiological study of dermatoses in pediatric age group in tertiary health care center in South Gujarat region - Sugat A Jawade; Vishal S Chugh; Sneha K Gohil; Amit S Mistry; Dipak D Umrigar (Indian Journal of Dermatology, 2015)
Background: Dermatologic conditions have different presentation and management in pediatric age group from that in adult; this to be studied separately for statistical and population based analysis. Objective: To study the pattern of various dermatoses in infants and children in tertiary health care center in South Gujarat region. Materials and Methods: This is a prospective study; various dermatoses were studied in pediatric patients up to 14 years of age attending the Dermatology OPD of New Civil Hospital, Surat, Gujarat over a period of 12 months from June 2009 to June 2010. All patients were divided into four different study groups: <1 month (neonates), 1 month to 1 year, >1 to 6 years and 7 to 14 years. Results: There were 596 boys and 425 girls in total 1021 study populations. Majority of the skin conditions in neonates were erythema toxicum neonatorum (12.97%), scabies (9.92%), mongolian spot (9.16%), and seborrheic dermatitis (7.63%). In > 1 month to 14 years age group of children among infectious disorder, children were found to be affected most by scabies (24.49%), impetigo (5.96%), pyoderma (5.62%), molluscum contagiosum (5.39%), tinea capitis (4.49%), leprosy (2.02%), and viral warts (1.35%) while among non-infectious disorders, they were affected by atopic dermatitis (4.27%), pityriasis alba (4.16%), seborrheic dermatitis (3.60%), pityriasis rosea (3.15%), others (3.01%), phrynoderma (2.70%), lichen planus (2.58%), contact dermatitis (1.57%) and ichthyosis (1.45%). Conclusion: There is a need to emphasize on training the management of common pediatric dermatoses to dermatologists, general practitioners and pediatricians for early treatment.